Level of galectin-3 and ST2 in ischemic chronic heart failure depending on the functional state of kidneys - V. D. Syvolap; , D. A. Lashkul (Zaporožskij Medicinskij Žurnal)
Aim. The aim of the study was to investigate the characteristics of level markers of fibrosis galectin-3 (Gal-3), ST2 in patients with ischemic chronic heart failure (CHF) depending on the glomerular filtration rate.